Flexural Strength and Behavior of Reinforced Izocrete Light Weight - ., Aso A. Faqe Rahim; ., Muhamad R. Abdulqadir (Iraqi Journal of Civil Engineering, 2022)
This study describes the results of tests carried out in order to investigate the structural behavior of reinforced concrete beams containing Expanded Polystyrene (EPS) stabilized Polystyrene beads. Three concrete mixtures were used with densities 350kg/m3, 500 kg/m3 and 600 kg/m3. A total of 12 beams, with control specimens were tested after 28 days of curing immersion in water. Four types of steel reinforcement were utilized: Two ratios of tensile steel reinforcement without compression steel and the same two ratios of tensile reinforcement with compression steel and stirrups. The beams were tested under 4- points loading up to failure. The main variables considered in this study were: different types of Izocrete densities and types of reinforcement steel bars. The results indicated that the amount of polystyrene beads significantly affects the strength of the concrete produced. In general, it can be observed that the compression, tensile and flexure strengths decreased as the EPS beads contents increased, and the moment capacity of the beams reduced with the increase of the beads ratio.The load deflection behavior of the Izocrete beams were similar to other lightweight concrete beams .The failure in most of the beams was initiated at the compression region undergoing large deformation due to the high compressibility of the material.